A cross-sectional study of the nutritional quality of student canteen purchases from New South Wales primary-school canteens. Issue 16 (25th July 2019) - Delaney, Tessa; Sutherland, Rachel; Wyse, Rebecca; Wolfenden, Luke; Lecathelinais, Christophe; Janssen, Lisa; Reilly, Kathryn; Wiggers, John; Lin Yoong, Sze
Abstract: Objective: To assess the nutritional quality of student canteen purchases at recess and lunch, including: (i) the mean energy (kilojoules), saturated fat (grams), total sugar (grams) and Na (milligrams) and percentage of energy from saturated fat and total sugar; and (ii) the proportion and types of foods purchased that are healthier (green) and less healthy (amber/red) according to a state school canteen policy. Design: A cross-sectional study of student canteen food and beverage recess and lunch purchases. Setting: Twenty-six randomly selected government primary schools that were non-compliant with a state school canteen policy from a region of New South Wales, Australia, were approached to participate. Participants: Students (aged 5–12 years) of participating schools. Results: Eighteen schools (69 %) consented to participate. On average students' recess purchases contained 571·2 kJ energy, 1·6 g saturated fat, 11·6 g total sugar and 132·4 mg Na with 10·0 % of energy from saturated fat and 37·8 % of energy from total sugar. Students' lunch purchases contained 685·4 kJ energy, 1·8 g saturated fat, 12·7 g total sugar and 151·4 mg Na with 9·5 % of energy from saturated fat and 31·8 % of energy from total sugar. Less healthy items represented 72 and 76 % of all items purchased at recess and lunch, respectively, with 'savoury snacks' and 'sugar-sweetened ice blocks and slushies' being the most common recess and lunch purchases, respectively. Conclusions: There is considerable scope to improve the nutritional quality of student purchases from primary-school canteens, with a high percentage of energy from total sugar. Future research is required to identify effective strategies to enhance compliance with canteen policies and support the purchase of healthier foods from school canteens.